Relational research of sport practice in schoolchildren depending on gender - Chacón Cuberos, R.; Arufe Giráldez, V.; Cachón Zagalaz, J.; Zagalaz Sánchez, Mª L.; Castro García, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
Insomuch as physical activity has taken a center stage as a way to prevent sedentary lifestyles, it is essential to know what are the sports which are played by schoolchildren outside schools. Therefore, this descriptive and cross-sectional research, conducted on a sample of 818 schoolchildren, has as a main objective to establish sport habits according to gender, which has acted as a moderating factor throughout history. The results showed that female schoolchildren practiced mainly individual sports and as a leisurely activity while men preferred collective and federated sports. Moreover, the level of sport practice determined that male students practiced more sports than female students, so in a greater number of weekly days and longer sessions. Therefore, this research demonstrates that the sport, which is played by children, depends on gender, as well as the necessity of matching this practice avoiding stereotypes and sedentary lifestyles.